Characterization of Chicken Tumor Necrosis Factor-α, a Long Missed Cytokine in Birds - Rohde, Franziska; Schusser, Benjamin; Hron, Tomáš; Farkašová, Helena; Plachý, Jiří; Härtle, Sonja; Hejnar, Jiří; Elleder, Daniel; Kaspers, Bernd (Frontiers in immunology, 2018)
Tumor necrosis factor-α (TNF-α) is a pleiotropic cytokine playing critical roles in host defense and acute and chronic inflammation. It has been described in fish, amphibians, and mammals but was considered to be absent in the avian genomes. Here, we report on the identification and functional characterization of the avian ortholog. The chicken TNF-α (chTNF-α) is encoded by a highly GC-rich gene, whose product shares with its mammalian counterpart 45% homology in the extracellular part displaying the characteristic TNF homology domain. Orthologs of chTNF-α were identified in the genomes of 12 additional avian species including Palaeognathae and Neognathae, and the synteny of the closely adjacent loci with mammalian TNF-α orthologs was demonstrated in the crow (Corvus cornix) genome. In addition to chTNF-α, we obtained full sequences for homologs of TNF-α receptors 1 and 2 (TNFR1, TNFR2). chTNF-α mRNA is strongly induced by lipopolysaccharide (LPS) stimulation of monocyte derived, splenic and bone marrow macrophages, and significantly upregulated in splenic tissue in response to i.v. LPS treatment. Activation of T-lymphocytes by TCR crosslinking induces chTNF-α expression in CD4+ but not in CD8+ cells. To gain insights into its biological activity, we generated recombinant chTNF-α in eukaryotic and prokaryotic expression systems. Both, the full-length cytokine and the extracellular domain rapidly induced an NFκB-luciferase reporter in stably transfected CEC-32 reporter cells. Collectively, these data provide strong evidence for the existence of a fully functional TNF-α/TNF-α receptor system in birds thus filling a gap in our understanding of the evolution of cytokine systems.
Keywords: biological activity; vrány; chicken; kultivované buňky; missing gene; Sequence Alignment; avian; Tumor Necrosis Factor-alpha; NF-kappa B; Avian Proteins; tumor necrosis factor-α; Receptors, Tumor Necrosis Factor; kur domácí; tumor necrosis factor-α receptors; Cloning, Molecular; TNF-alfa; Cells, Cultured; GC Rich Sequence; Macrophages; Chickens; zvířata; GC bohatá sekvence; receptory TNF; Humans; Mammals; savci; Crows; ptačí proteiny; klonování DNA; makrofágy; CD4-pozitivní T-lymfocyty; sekvenční seřazení; Palaeognathae; CD4-Positive T-Lymphocytes; lidé; Animals